1999
DOI: 10.1093/bja/83.6.872
|View full text |Cite
|
Sign up to set email alerts
|

Interscalene brachial plexus anaesthesia with 0.5%, 0.75% or 1% ropivacaine: a double-blind comparison with 2% mepivacaine

Abstract: We have compared interscalene brachial plexus block performed with ropivacaine or mepivacaine in 60 healthy patients undergoing elective shoulder surgery. Patients were allocated randomly to receive interscalene brachial plexus anaesthesia with 20 ml of 0.5% ropivacaine (n = 15), 0.75% ropivacaine (n = 15), 1% ropivacaine (n = 15) or 2% mepivacaine (n = 15). Readiness for surgery (loss of pinprick sensation from C4 to C7 and inability to elevate the limb from the bed) was achieved sooner with 1% ropivacaine (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 13 publications
3
42
0
Order By: Relevance
“…Duration of analgesia in our study correlated with studies by Conolly C 4 and Laura Bertini et al 20 Casati et al, 21 Vaghadia et al, 19 Chandini M Soni 18 and Tripathi D et al 22 where they found no statistically significant differences between the two drugs.…”
Section: Variablessupporting
confidence: 90%
“…Duration of analgesia in our study correlated with studies by Conolly C 4 and Laura Bertini et al 20 Casati et al, 21 Vaghadia et al, 19 Chandini M Soni 18 and Tripathi D et al 22 where they found no statistically significant differences between the two drugs.…”
Section: Variablessupporting
confidence: 90%
“…13 Similar observation was made by Casati et al who worked on brachial plexus block performed with Ropivacaine or Mepivacaine in 60 healthy patients undergoing elective upper limb surgery. 14 In the present study, the onset of motor block was earlier in study group of dexamethasone having the mean value of 18.700±2.718min and in comparison, the control group had a mean value of 17.966±2.747min. which is statistically significant (p>0.05).…”
Section: Resultssupporting
confidence: 47%
“…Similar onset times (1 to 3.2 minutes) were recorded with 0.5% ropivacaine injected supraperiosteally for maxillary anesthesia. 6 Some investigators 5,11,12 have confirmed that increasing the concentration of ropivacaine reduces the onset time of peripheral nerve block, presumably because more local anesthetic molecules are available to penetrate the nerve per unit time. Akerman and associates 1 attributed ropivacaine's tendency toward a more rapid onset of action in comparison with bupivacaine to its weaker binding to extraneural fat and tissues and to its greater availability for transfer to the site of action in the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Axillary brachial plexus block with ropivacaine provides adequate anesthesia for hand surgery 3 ; interscalene brachial plexus block with ropivacaine produces rapid onset of anesthesia and prolonged postoperative analgesia nearly twofold longer than with mepivacaine. 5 Limited data are available concerning the use of ropivacaine in dental practice. It has been demonstrated that ropivacaine is equivalent in potency and efficacy to bupivacaine (both with 1 : 200,000 epinephrine) for maxillary anterior filtration.…”
mentioning
confidence: 99%